Relationship between Islamic Human Resources Management (IHRM) practices and trust: An empirical study - Nik Mutasim Nik Abd Rahman; Mohamad Adnan Alias; Sharmin Shahid; Mohamad Abdul Hamid; Syed Shah Alam (Journal of Industrial Engineering and Management (JIEM), 2013)
Purpose: The purpose of this study is to explore and examines the theoretical frameworks of Islamic human resource management practices and trust in organization. Additionally, to investigate the extent to which Islamic HRM practices inspire and revival employees trust in organization. Design/methodology/approach: This study comprised sample of 236 Islamic Bank employees in Bangladesh. A cross-sectional research design was used to examine the relationship between Islamic Human Resource Management practices and trust. Data were gathered based on personal administered questionnaire. Findings and Originality/value: This study results show that knowledge, understanding and practices of Islamic principles, recruitment and selection, training and development, and reward system significantly related to the trust. But performance appraisal are found have insignificant relationship. Research limitations/implications: The data for this study are collected by self-administered questionnaire, a method with well-known shortcomings. Second, this study concentrated on the Islamic bank employees in Bangladesh. Practical implications: An important implication of this research is that the interesting findings give some insight to the management of Islamic bank to focus on improving Islamic Human Resource Management practices, in their all kind of management, as that could improve their trust in the bank. Originality/value: The findings are original and unique and are based on the literature from different researches. The results are based on a sample of Islamic Bank employees in Bangladesh. The research findings are useful to academics and management of Islamic bank all over the world.
Keywords: 650; Islamic Human Resource Management (IHRM); trust in organization; Islamic Banks; Bangladesh